Proximal digit tip amputation initiates simultaneous blastema and transient fibrosis formation and results in partial regeneration. Issue 1 (21st August 2020) - Dawson, Lindsay A.; Schanes, Paula P.; Marrero, Luis; Jordan, Kathryn; Brunauer, Regina; Zimmel, Katherine N.; Qureshi, Osama; Imholt, Felisha M.; Falck, Alyssa R.; Yan, Mingquan; Dolan, Connor P.; Yu, Ling; et al.
Abstract: Complete extremity regeneration in mammals is restricted to distal amputations of the digit tip, the terminal phalanx (P3). In mice, P3 regeneration is mediated via the formation of a blastema, a transient population of progenitor cells that form from the blending of periosteal and endosteal/marrow compartmentalized cells that undergo differentiation to restore the amputated structures. Compartmentalized blastema cells are formed independently, and periosteal compartment‐derived cells are required for restoration of amputated skeletal length. P3 regenerative capacity is progressively attenuated at increasingly more proximal amputation levels, eventually resulting in regenerative failure. The continuum of regenerative capacity within the P3 wound milieu is a unique model to investigate mammalian blastema formation in response to distal amputation, as well as the healing response associated with regenerative failure at proximal amputation levels. We report that P3 proximal amputation healing, previously reported to result in regenerative failure, is not an example of complete regenerative failure, but instead is characterized by a limited bone regeneration response restricted to the endosteal/marrow compartment. The regeneration response is mediated by blastema formation within the endosteal/marrow compartment, and blastemal osteogenesis progresses through intramembranous ossification in a polarized proximal to distal sequence. Unlike bone regeneration following distal P3 amputation, osteogenesis within the periosteal compartment is not observed in response to proximal P3 amputation. We provide evidence that proximal P3 amputation initiates the formation of fibrotic tissue that isolates the endosteal/marrow compartment from the periosteal compartment and wound epidermis. While the fibrotic response is transient and later resolved, these studies demonstrate that blastema formation and fibrosis can occur in close proximity, with the regenerative response dominating the final outcome. Moreover, the results suggest that the attenuated proximal P3 regeneration response is associated with the absence of periosteal‐compartment participation in blastema formation and bone regeneration.